KARAKTERISTIK SOUND TRANSMISSION LOSS PINTU AKUSTIK YANG DIGUNAKAN SEBAGAI PENGHALANG KEBISINGAN - Achmad Suandi (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2009)
This paper presents the sound transmission through acoustic doors. In addition, the possibility of an appreciable sound leak on the acoustic door is briefly discussed. Characterization of two different types of acoustic doors has been done, namely single and double opening acoustic doors. Acoustic door is frequently used to reduce noise level inside a room, which is emitted from noise sources, such as blower, generator set, industrial machinery, etc. Excellent acoustic quality can be achieved by acoustic doors which can produce high sound transmission class values (STC). The STC values can be measured by sound transmission loss tests. The sound transmission loss tests for both acoustic doors were carried out in the noise source and receiving rooms at Acoustic Laboratory of Puslit KIM-LIPI, Serpong. Based on the measurement results, it was proved that single opening acoustic door produced higher STC values than that of double opening acoustic door. The single opening acoustic door had an STC of 49 dB, whereas the double opening acoustic door resulted in STC of 47 dB.